An oil-absorber-bioscrubber system to stabilize biotreatment of pollutants present in waste gas. Fluctuating loads of 1,2-dichloroethane - Koutinas, Michalis; Martin, James; Peeva, Ludmila G.; Mantalaris, Athanasios A.; Livingston, Andrew G (My University, 2006)
Biotreatment technologies offer a cost-effective and efficient method for dealing with point-source releases of solvents. However, a major problem hampering these technologies is the fluctuating pollutant loads, which is especially critical for inhibitory pollutants. Provision of biotreatment systems able to cope with this problem is a significant technological and environmental challenge. This study investigates the potential for an absorber to act as buffer for shock loadings of inhibitory pollutants in waste-gas streams undergoing biological treatment. 1,2-Dichloroethane (DCE) was used as an example of a toxic and inhibitory organic pollutant. The stability of a combined oil-absorber-bioscrubber (OAB) system was compared to that of a bioscrubber only (BO) system when each was subjected to shock loads of DCE. The BO system was inoculated with Xanthobacter autotrophicus strain GJ10 and was submitted to sharp, sequential pulses in DCE inlet load, which caused system instability. Complete inhibition of the BO process occurred for a 3 h DCE pulse, leading to 9125 g of DCE m(-3)bioscrubber total organic discharged (TODDCE). Following the pulse, fluorescence in situ hybridization (FISH) showed that the active strain GJ10 was effectively washed-out. In contrast, the performance of the OAB system was stable during DCE shock loads. The carbon dioxide production remained stable, and low levels of effluent DCE and total organic carbon concentrations were found. For the 3 h pulse TODDCE was only 173 g of DCE m(-3)bioscrubber, and FISH indicated that the GJ10 strain remained active. We conclude that the OAB system offers an effective solution to the biological treatment of waste-gas containing fluctuating pollutant concentrations.
Keywords: Air pollution; Carbon dioxide; Cost effectiveness; Ethane; Wastes